Literature Study: The Impact of Green Financial Reports, Environmental Policies, and ESG Performance on Corporate Sustainability Reporting - Chandra, Muhammad Mahardika; Tambunan, Dame Romauli; Rambe, Hasvia Sheilla Aldira; Nuraini, Nuraini; Sitompul, Monika Pebri Yanti; Arnita, Vina (Jurnal Riset Ilmu Pendidikan, 2024)
This study aims to explore the relationship between green financial reporting, environmental policies, and Environmental, Social, and Governance (ESG) performance on corporate sustainability reporting. Using a literature review method, this research integrates findings from previous studies published in relevant accredited national journals. The analysis reveals that green financial reporting plays a crucial role in enhancing corporate transparency and reputation. Strong environmental policies support sustainability reporting by providing strategic guidelines for managing the ecological impact of corporate operations. Additionally, ESG performance serves as a key indicator for assessing corporate sustainability, adding value through operational efficiency and attractiveness to investors. The study also finds that implementing green accounting positively impacts profitability and corporate image, although green financing adoption faces challenges due to its initial implementation stages. This research emphasizes the importance of integrating sustainability reporting to create long-term value for companies, stakeholders, and the environment.